INTERAKSI MANUSIA DAN LINGKUNGAN DALAM PERSPEKTIF ANTROPOSENTRISME, ANTROPOGEOGRAFI DAN EKOSENTRISME: Human and Environment Interactive in the Perspective of Antroposentrism, Antropogeography and Ecocentrism - Raden Mas Sukarna (HUTAN TROPIKA, 2021)
Humans and environment are always interaction due to they occupy the same spacebased on the rules of both interdependence and adaptation that is tied to a natural balancesystem. Human interactions have to adapt to sustain life and exploit the natural resourcesaround them that produce cultural landscapes which are inseparable from thecharacteristics area. The strong influence of nature in determining the socio-culturalconditions of humans has led to anthropogeography. In line with the rapidly increasingnumber of people including their minds are also developing science and technology toobtain the necessary of their life. Humans have not a sense of being part of the socio-biogeophysical system, but are separate and stand outside of its and produceanthropocentrism. These phenomena have produced the idea that have to be aharmonious and balanced relationship between human necessary and the naturalresources capability. This means that human has to recognize their survival and otherspecies depend on ecological principles. Thus, human necessary should be carried out inan integrated with the other species necessary that produce an ecocentrism that respect tonature.Keywords: Human, environment, interaction, anthropocentrism, anthropogeography,ecocentrism